Identification of gene features important for post-transcriptional regulation of Plasmodium falciparum invasion genes. - Goh, Zewei. (2009)
Plasmodium falciparum, the major cause of human malaria, is able to up-regulate various ligands to invade erythrocytes possessing different receptors in a process known as invasion-pathway switching. Recent evidence from the W2mef P. falciparum clone has shown that this switch involves the post-transcriptional regulation (PTR) of many invasion-related genes in addition to previously characterized mechanisms. To identify gene features responsible for this PTR, the 5’ un-translated regions (UTR) of 7 genes up-regulated at the protein level were cloned into luciferase-reporter plasmids and then transfected into both normal W2mef and W2mef clones that had switched invasion pathways. No difference in luciferase activity was observed between transfected switched and un-switched clones, suggesting that motifs within the 5’ UTR of invasion genes are either not responsible for, or insufficient to drive PTR in P. falciparum.